Alto medioevo mediterraneo - Stefano, Gasparri (Reti Medievali E-Book, 2005)
This book, generated by the encounter between two schools - the Italian early mediaeval and the Argentine late antique - ranges from Italy to Gaul and the Eastern Mediterranean over a timespan from the third/fourth to the eighth centuries. It introduces a world polarised between an East destined to be divided between Byzantium and Islam, and a West composed of the post-Roman barbarian societies. The East, rooted within the Roman-Hellenistic heritage, represents a source of religious experiences which profoundly influence the West. With reference to Italy, the study focuses on an analysis of the Episcopal network, the emergence of the Benedictine Rule, and the correspondence of Gregory the Great. In the passage from East to West, the 'new' Barbarian societies emerge in the front line, proving that they too were seeking out ancient roots, both in Gaul and in Italy, the latter being partly still linked to Byzantium and partly under the dominion of the Lombards. Finally various crucial aspects of the Lombard kingdom - which proves to be profoundly permeated by the legacy of Rome - are addressed, including royalty, the capitals and the law, through the analysis of both written and archaeological sources.